The Relationship between the Hydrolysis Degree and Calcium-Binding Capacity of Whey Protein by Enzymatic Hydrolysis - Huang, Shun Li; Huang, Yi Fan; Zhao, Li Na; Wang, Shao Yun (Applied Mechanics and Materials, 2014)
To study the relationship between the hydrolysis degree and calcium-binding capacity of whey protein by enzymatic hydrolysis, the response surface method was firstly used to investigate optimized the hydrolysis conditions of whey protein with protamex and flavorzyme. The optimum process parameters for the whey protein hydrolysis were as follows: Whey protein concentration was 5.0% (w/v), the ratio of protease to whey protein was 4.0% (w/w), the mass ratios of protamex to flavorzyme (w/w) was 2:1, and the reaction temperature was 49 °C. The hydrolysate obtained after the hydrolysis of 7 h, with a hydrolysis degree of 25.92%, possessed the highest Ca-binding capacity of 27.92%. Finally, the relationship between the hydrolysis degree and calcium-binding capacity was established and whey protein hydrolysate with high calcium-binding capacity was prepared, which can provide basic theories for the following optimization of chelation of whey protein hydrolysate with calcium.